PENERAPAN METODE PEMBELAJARAN BERDIFERENSI UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SMP NASIONAL MAKASSAR - Hasryana B; Wahab, Abdul; Subaedah; Mustamin; Raehana, Syarifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students’ learning outcomes through the implementation of a differentiated learning model in Islamic Education for Grade VII A at SMP Nasional Makassar. The research employed a Classroom Action Research (CAR) design conducted in two cycles, namely Cycle I and Cycle II. Each cycle consisted of planning, action, observation, and reflection stages. The research subjects were 32 students of Grade VII A. Data were collected through observation of teacher and student activities, learning achievement tests, and documentation. Data analysis was carried out using descriptive quantitative and qualitative techniques to examine improvements in both the learning process and learning outcomes. The results indicate that the implementation of the differentiated learning model significantly improved students’ engagement and learning outcomes. In the pre-cycle stage, only 31% of students achieved learning mastery, with an average score of 62.35. After the application of differentiated learning in Cycle I, learning mastery increased to 59% with an average score of 76.41. Furthermore, in Cycle II, which emphasized product differentiation, learning mastery showed a more substantial improvement, reaching 87.5% with an average score of 88.13. In addition, observation results revealed an increase in students’ learning readiness and participation, from 52% in Cycle I to 86% in Cycle II. Based on these findings, it can be concluded that the differentiated learning model is effective in improving students’ learning outcomes in Islamic Education for Grade VII A at SMP Nasional Makassar.